PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT. TELKOM AKSES KOTA MAKASSAR - Rani Rani; Ihyani Malik; Nurbiah Tahir (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
This study aims to determine the organizational culture and employee performance at PT Telkom Akses Makassar City, as well as the effect of organizational culture on employee performance. This quantitative research uses explanatory research with a sample of 133 out of 200 employees, taken using the Slovin formula. Data were collected through questionnaires and analyzed with SPSS V.27. The results show that organizational culture is good, with norm implementation as the dominant indicator (59%), and employee performance is also good, with quality as the dominant indicator (59.13%). Hypothesis testing showed a p-value